Study on gas accumulation conditions of continental shale in Es3 member in the northern dongpu depression, eastern China - Zhang, Peng; Deng, Ende; Yang, Junwei; Huang, Yuqi; Tang, Xuan; Liu, Chengwei (Frontiers in Earth Science, 2022)
The organic-rich shales in the northern Dongpu Depression were deposited in deep and semi-deep lakes based upon evidence from the geochemical characteristic and rock mineral of the Es3 member. The results show that these rocks gradually decrease in organic matter abundance and deterioration of organic matter types from the center of the salt lake towards the edges. The development of high-quality shales in Es3 member is due to stratified sedimentation of a deep water, narrow basin water body. The saline lake region has a high TOC content, primarily type I derived from low-grade aquatic organisms. The minerals consist of a variety of mainly clay minerals (31-71%), quartz (11.2-57.9%), plagioclase (3.3-22.1%), dolomite (1.8-19.9%), and pyrite (1-4.1%).The water body was mainly brackish to super-brackish, which has strong limitations and severe salinity stratification, resulting in stable anoxic conditions of the bottom water and conducive to preserving organic matter. The shales were divided into massive silty shale facies, laminated paste shale facies, and laminated gray shale facies according to the mineral composition and microstructure. Comparing the geochemical characteristics, the laminated calcareous shale lithofacies of the deep to semi-deep lacustrine environments are favorable for shale oil and gas occurrence. Pores consist of inorganic pores (intergranular mineral pores, dissolution pores, clay mineral interlayer cracks, mineral intergranular pores micropores, dissolution pores, clay mineral layer cracks, and cracks) with relatively few organic pores.There are many types of natural gas in the study area. The oil-type gas came from the lacustrine shale rock in Es3 member of Shahejie Formation, the coal-derived gas came from the high mature coal-based gas in the deep Carboniferous-Permian system, and the mixed gas was the mixed source of the above two source rocks.Multiple sets of overlying halite provided adequate seals within the depression and were conducive to the accumulation and preservation of hydrocarbons throughout the basin.